Response of grassland ecosystem function to plant functional traits under different vegetation restoration models in areas of karst desertification - Song, Shuzhen; Xiong, Kangning; Chi, Yongkuan (Frontiers in Plant Science, 2023)
Plant functional traits serve as a bridge between plants, the environment, and ecosystem function, playing an important role in predicting the changes in ecosystem function that occur during ecological restoration. However, the response of grassland ecosystem function to plant functional traits in the context of ecological restoration in areas of karst desertification remains unclear. Therefore, in this study, we selected five plant functional traits [namely, plant height (H), specific leaf area (SLA), leaf dry matter content (LDMC), root length (RL), and root dry matter content (RDMC)], measured these along with community-weighted mean (CWM) and functional trait diversity, and combined these measures with 10 indexes related to ecosystem function in order to investigate the differences in plant functional traits and ecosystem function, as well as the relationship between plant functional traits and ecosystem functions, under four ecological restoration models [Dactylis glomerata (DG), Lolium perenne (LP), Lolium perenne + Trifolium repens (LT), and natural grassland (NG)]. We found that: 1) the Margalef index and Shannon–Wiener index were significantly lower for plant species in DG and LP than for those in NG (P<0.05), while the Simpson index was significantly higher in the former than in NG (P<0.05); 2) CWMH, CWMLDMC, and CWMRDMC were significantly higher in DG, LP, and LT than in NG, while CWMSLA was significantly lower in the former than in NG (P<0.05). The functional richness index (FRic) was significantly higher in DG and LP than in NG and LT, but the functional dispersion index (FDis) and Rao’s quadratic entropy index (RaoQ) were significantly lower in DG and LP than in NG and LT (P<0.05), and there was no significant difference between DG and LP, or between NG and LT (P>0.05); 3) ecosystem function, including ecosystem productivity, carbon storage, water conservation and soil conservation, was highest in LT and lowest in NG; and 4) CWMLDMC (F=56.7, P=0.024), CWMRL (F=28.7, P=0.024), and CWMH (F=4.5, P=0.048) were the main factors affecting ecosystem function. The results showed that the mixed pasture of perennial ryegrass and white clover was most conductive to restoration of ecosystem function. This discovery has important implications for the establishment of vegetation, optimal utilization of resources, and the sustainable development of degraded karst ecosystems.